Bacillus cytotoxicus Genomics: Chromosomal Diversity and Plasmidome Versatility - Fayad, Nancy; Koné, Klèma Marcel; Gillis, Annika; Mahillon, Jacques (Frontiers in Microbiology, 2021)
Bacillus cytotoxicus is the thermotolerant representative of the Bacillus cereus group. This group, also known as B. cereus sensu lato, comprises both beneficial and pathogenic members, and includes psychrotolerant and thermotolerant species. B. cytotoxicus was originally recovered from a fatal outbreak in France in 1998. This species forms a remote cluster from the B. cereus group members and reliably contains the cytk-1 gene, coding for a cytotoxic variant of cytotoxin K. Although this species was originally thought to be homogenous, intra-species diversity have been recently described with four clades, six RAPD patterns and eleven plasmids profiles. This study aimed to get new insights into the genomic diversity of B. cytotoxicus and to decipher the underlying chromosomal and plasmidial variations among six representative isolates through whole genome sequencing. Among the six sequenced strains, four fitted the previously described genomic clades A and D, while the remaining two constituted new distinct branches. As for the plasmid content of these strains, three large plasmids were putatively conjugative and three small ones potentially mobilizable, harbouring coding genes for putative leaderless bacteriocins. Mobile genetic elements such as prophages, Insertion Sequences (IS) and Bacillus cereus repeats (bcr) greatly contributed to the B. cytotoxicus diversity. As for IS elements and bcr, IS3 and bcr1 were the most abundant elements, and, along with the group II intron B.c.I8, were found in all analysed B. cytotoxicus strains. When compared to other B. cytotoxicus strains, the type-strain NVH 391-98 displayed a relatively low number of IS. Our results shed new light on the contribution of mobile genetic elements to the genome plasticity of B. cytotoxicus and their potential role in horizontal gene transfer.